Food security outcomes in agricultural systems models: Current status and recommended improvements. (March 2021) - Nicholson, Charles F.; Stephens, Emma C.; Kopainsky, Birgit; Jones, Andrew D.; Parsons, David; Garrett, James
Abstract: Improvement of food security is a common objective for many agricultural systems analyses, but how food security has been conceptualized and evaluated within agricultural systems has not been systematically evaluated. We reviewed the literature on agricultural systems analyses of food security at the household- and regional-levels, finding that the primary focus is on only one dimension of food security—agricultural output as a proxy for food availability. Given that food security comprises availability, access, utilization and stability dimensions, improved practice would involve more effort to incorporate food access and stability indicators into agricultural systems models. The empirical evidence base for including food access indicators and their determinants within agricultural systems models requires further development through appropriate short and long-term investments in data collection and analysis. Assessment of the stability dimension of food security (through time) is also particularly under-represented in previous work and requires the development and application of appropriate dynamic models of agricultural systems that include food security indicators, coupled with more formalized treatment of robustness and adaptability at both the regional and household levels. We find that agricultural systems models often conflate analysis of food security covariates that have the potential to improve food security (like agricultural yields) with an assessment of food security itself. Agricultural systems modelers should exercise greater caution in referring to analyses of agricultural output and food availability as representing food security more generally. Graphical abstract: Unlabelled Image Highlights: Many agricultural systems model analyses are motivated by food security outcomes but use a diverse set of food security metrics. We summarized and assessed the use of food security metrics in N = 91 household and N = 26 regional models identified in SCOPUS. Food availability metrics such as yields or production are more commonly used in agricultural systems models than access or stability indicators. Analyses with agricultural systems models should avoid equating food availability with food security. Improved representation of food security outcomes should focus on food access metrics such as experiential scales or food consumption expenditures.